Equitable Culture in Cultural Environments (Cadernos de Sociomuseologia, 2024)
The culture of equity is conceived, internalized, cultivated, and multiplied through sharing, it is developed, tested, applied, and validated in its implementation within the family, the community, and society, presenting itself to citizens, whether with various disadvantages or anomalies or without such limitations, as a challenging yet rewarding mission of social motivation, research, and investigation, as a mission characterized by natural fluidity in sensitivity and openness to mutual acceptance and understanding of one another, adapting everything to everyone in terms of accessibility and usability in the world.The culture of equity, as a unifying expression of sensitivities and achievements for the common good in society, demands a mutual and strong scientific and compassionate awareness in its realization, as a long and joyful journey, driven by passion in the progressive attainment of success through stages, with the understanding that "nothing great in the world is accomplished without passion" (Hegel).Keywords: Culture; Equity; Multisensoriality; Socioeducommunication; Typhlology; Typhloscience.